Effect of Exogenous Melatonin Application on the Grain Yield and Antioxidant Capacity in Aromatic Rice under Combined Lead–Cadmium Stress - Ye Jiang; Suihua Huang; Lin Ma; Leilei Kong; Shenggang Pan; Xiangru Tang; Hua Tian; Meiyang Duan; Zhaowen Mo (Antioxidants, 2022)
This study aimed to determine the mechanism of exogenous melatonin application in alleviating the combined Pb and Cd (Pb-Cd) toxicity on aromatic rice (Oryza sativa L.). In this study, a pot experiment was conducted; two aromatic rice varieties, Yuxiangyouzhan and Xiangyaxiangzhan, were selected, and sprays using 50, 100, 200, and 400 μmol L−1 melatonin (denoted as S50, S100, S200, and S400) and irrigation using 100, 300, and 500 μmol L−1 melatonin (denoted as R100, R300, and R500) were also selected. The results showed that, under the S50, S100, and S200 treatments, the Pb content of aromatic rice grain decreased, and the grain yield increased significantly. Moreover, the application of exogenous melatonin significantly reduced the accumulation of H2O2 in rice leaves at maturity under Cd–Pb stress and reduced the MDA content in Xiangyaxiangzhan leaves. In addition, the microbial community structure changed significantly under S50 and R300 treatments. Some pathways, such as the synthesis of various amino acids and alanine, aspartate, and glutamate metabolism, were regulated by S50 treatment. Overall, melatonin application improved aromatic rice grain yield while reducing heavy metal accumulation by regulating the antioxidant capacity and metabolites in aromatic rice plants and altering the physicochemical properties and microbial community structures of the soil.